Innate Immunity to Campylobacter jejuni in Guillain‐Barré Syndrome. Issue 3 (30th June 2015) - Huizinga, Ruth; van den Berg, Bianca; van Rijs, Wouter; Tio‐Gillen, Anne P.; Fokkink, Willem Jan R.; Bakker‐Jonges, Liesbeth E.; Geleijns, Karin; Samsom, Janneke N.; van Doorn, Pieter A.; Laman, Jon D.; Jacobs, Bart C.
<x xml:space="preserve">Abstract</x> Objective Guillain‐Barré syndrome (GBS) is a postinfectious neuropathy most frequently caused by Campylobacter jejuni. Lipo‐oligosaccharides (LOS), expressed by C. jejuni induce antibodies that cross‐react with self‐glycolipids in peripheral nerves, causing neuropathy. Less than 1 in 1, 000 persons infected with C. jejuni develop GBS, and the factors that determine GBS susceptibility are poorly understood. We hypothesized that these persons have a high intrinsic dendritic cell (DC) response to C. jejuni LOS through Toll‐like receptor 4 (TLR4) activation. Methods Intrinsic DC responsiveness to C. jejuni LOS was investigated first in 20 healthy controls at three time points with a 3‐month interval, and second in patients, who previously developed GBS after a C. jejuni infection (n = 27) and controls (n = 26). Results The DC response to C. jejuni LOS was highly variable between, but not within, healthy individuals, suggesting that intrinsic factors determine the magnitude of TLR4‐mediated innate response. High responsiveness to C. jejuni LOS by former GBS patients was evidenced by increased expression of CD38 and CD40. Frequency of CD38, CD40 and type I interferon high responders was significantly increased in the GBS group. Interpretation These results suggest that a strong response to TLR4 stimulation is a critical host condition for the development of GBS after an infection with C. jejuni. Ann Neurol 2015;78:343–354